Single mode to dual mode switch through a THz reconfigurable metamaterial - Zhang, Wu (2018)
Metamaterials interact with incident electromagnetic waves through their consisting subwavelength metamolecules. In this paper, we reported a reconfigurable metamaterial which tunes its THz response experimentally from a single mode resonance at 2.99 THz to a dual mode resonance at 2.94 THz and 2.99 THz. The reconfiguration is realized through a micromachined actuator, and the tunability is achieved by breaking the symmetry of the metamolecule. An abrupt change in the transmission is experimentally observed when the gap between two metallic structures is closed, and a decrease in transmission from 40% to 5% at 2.94 THz is obtained. Such a tunable metamaterial promises widespread applications in optical switches, filters, and THz detectors.